2001
DOI: 10.1348/135910701169188
|View full text |Cite
|
Sign up to set email alerts
|

Social behaviour and illness information interact to influence the peer acceptance of children with chronic illness

Abstract: Social behaviour influences the peer acceptance of hypothetical children with chronic illness. Prosocial behaviour enhances acceptance of children described with illness, while aggressive behaviour hampers it. Additionally, prosocial behaviour is more beneficial, and aggressive behaviour is less damaging for children described as ill versus healthy. The potential processes by which peers judge acceptance of children with illness are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…Children with long term conditions are at a higher risk for emotional and behavioural problems (Hysing, Elgen, Gillberg, & Lundervold, 2009;Layte & McCrory, 2013). Social behaviour influences peer acceptance of children with long term conditions and social withdrawal and anxiety of chronically ill children who perceive themselves as different can interfere with development of social skills and thus, their social life (Alderfer, Wiebe, & Hartmann, 2001Pinquart & Shen, 2011b). As the desire to portray themselves as normal and not different from their peers can result in nonadherence to medical regimes, healthcare professionals' working with children with long term conditions need to be cognisant of the impact that perceiving themselves as different can have on this population.…”
Section: Discussionmentioning
confidence: 99%
“…Children with long term conditions are at a higher risk for emotional and behavioural problems (Hysing, Elgen, Gillberg, & Lundervold, 2009;Layte & McCrory, 2013). Social behaviour influences peer acceptance of children with long term conditions and social withdrawal and anxiety of chronically ill children who perceive themselves as different can interfere with development of social skills and thus, their social life (Alderfer, Wiebe, & Hartmann, 2001Pinquart & Shen, 2011b). As the desire to portray themselves as normal and not different from their peers can result in nonadherence to medical regimes, healthcare professionals' working with children with long term conditions need to be cognisant of the impact that perceiving themselves as different can have on this population.…”
Section: Discussionmentioning
confidence: 99%
“…In others, only careful analysis of the type of questions or statements used in the questionnaires revealed on which component(s) of attitude the questionnaire was focused. These analyses showed that only a few studies used the three-component theory as a framework and defined their questionnaires in terms of cognitive, affective, or behavioral aspects (Alderfer et al 2001;Beck et al 2006;Nowicki 2006). …”
Section: Conceptual Framework Of the Questionnairementioning
confidence: 99%
“…Cohen (1955) stressed that the most important goal of young people was not to become wealthy, but to gain status and become accepted in their peer groups. Chronic or frequent illnesses may influence a juvenile's ability to interact with his or her peers (Alderfer, Wiebe, & Hartmann, 2001) as may motor impairments (Fletcher, Larkin, & Hand, 2003). Health problems may lead some children to become outcasts since other youth may have been taught to avoid children who are ill.…”
Section: Health As Sources Of General Strainmentioning
confidence: 99%